KEKERASAN DALAM RUMAH TANGGA TERHADAP ANAK MENURUT PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Desa Janti Kecamatan Mojoagung Kabupaten Jombang) Indah Nur Cahyani - Indah Nur Cahyani; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2024)
ABSTRACT This research was motivated by the existence of domestic violence against children that had occurred in Janti Village, Mojoagung District, Jombang Regency. Looking after and caring for children well is the obligation of all parents, because children are a gift from Allah SWT. However, no family is free from problems or problems, there are various kinds of problems in families, one of which is violence against children. Children who are victims of violence will disrupt or affect the child's development. The type of research that the author uses in this thesis uses qualitative research. Qualitative research is field research carried out on objects or places. In this research, the author uses primary data sources, namely, data originating from related parties. For example, victims of domestic violence. From the results of this research it can be concluded that violence has a big impact on children's mental development in the future, because of the lack of love, attention and time from both parents. So that it affects the child's development, including the child becoming traumatized and more emotional, often crying, lacking self-confidence and feeling disappointed with situations that cause stress due to the problems they have experienced.